2017
DOI: 10.7554/elife.21763
|View full text |Cite
|
Sign up to set email alerts
|

Frequent exchange of the DNA polymerase during bacterial chromosome replication

Abstract: The replisome is a multiprotein machine that carries out DNA replication. In Escherichia coli, a single pair of replisomes is responsible for duplicating the entire 4.6 Mbp circular chromosome. In vitro studies of reconstituted E. coli replisomes have attributed this remarkable processivity to the high stability of the replisome once assembled on DNA. By examining replisomes in live E. coli with fluorescence microscopy, we found that the Pol III* subassembly frequently disengages from the replisome during DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
150
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(161 citation statements)
references
References 60 publications
(81 reference statements)
10
150
1
Order By: Relevance
“…Frequent polymerase exchange and uncoupled lagging‐strand synthesis have also been detected during E. coli replication. In contrast to the exchange of individual T7 polymerases, in E. coli , entire Pol III* (Pol III HE lacking β clamp) complexes exchange . Consistent with the variation seen in T7 polymerase number, more than one Pol III* subassembly has been detected at the replication fork .…”
Section: A Dynamic Interplay Drives Initiation Of Bacterial Dna Replimentioning
confidence: 64%
See 2 more Smart Citations
“…Frequent polymerase exchange and uncoupled lagging‐strand synthesis have also been detected during E. coli replication. In contrast to the exchange of individual T7 polymerases, in E. coli , entire Pol III* (Pol III HE lacking β clamp) complexes exchange . Consistent with the variation seen in T7 polymerase number, more than one Pol III* subassembly has been detected at the replication fork .…”
Section: A Dynamic Interplay Drives Initiation Of Bacterial Dna Replimentioning
confidence: 64%
“…The foundation of our understanding of replication mechanism derives from several seminal experiments conducted in the second half of the 20th century which suggested DNA replication is performed by a single static complex with highly defined operating principles. In contrast to this view, single‐molecule observations have revealed that dynamic exchange of core components, pausing events, and several types of DNA loops may underlie coordination of daughter‐strand synthesis . Individually, these events support different mechanistic models which cannot always be reconciled in a single reaction mechanism.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such a deterministic model violates fundamental chemical principles (van Oijen and Dixon, 2015), not to mention the pragmatism of evolution, and it has been challenged by three recent single-molecule studies that uncover alternate pathways. The first two studies demonstrate facile exchange between complete replicase units at the fork and in solution, on the seconds timescale, both in vivo (Beattie et al 2017) and in vitro (Lewis et al 2017). The third study (Graham et al 2017) suggests that even under conditions with no free polymerases in solution, the DnaB helicase can transiently uncouple and proceed more slowly ahead of the replicase at the apex of the replication fork.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial replisome is the prototype of a fixed structural assembly of both leading and lagging strand polymerases with the clamploader. However, recent studies indicate that there is a frequent exchange of the bacterial polymerase during replication [175]. In the case of Pol ε, a similar situation could exist in terms of disengagement, such that uncoupling might be more frequent than expected even in the absence of replication stress.…”
Section: Roles Of Pol δ4 and Pdip46 In Leading Strand Synthesismentioning
confidence: 98%